Show, don't tell: Education and physical exposure effects in remanufactured product markets - Abdulla, Huseyn; Abbey, James D.; Atalay, A. Selin; Meloy, Margaret G. (Journal of Operations Management, 2024)
We study the effectiveness of two theoretically and practically relevant interventions designed to increase familiarity with and thereby stimulate the appeal of and willingness to pay (WTP) for remanufactured (refurbished) consumer products that are often found repulsive by consumers: (1) educating consumers about the remanufacturing process, (2) providing physical exposure to remanufactured products. We find that education does not cause an increase in the appeal of and WTP for remanufactured consumer products. Providing physical exposure to remanufactured products, relative to text and text‐plus picture or video modalities, significantly increases both the appeal and WTP as a result of increasing perceived quality and decreasing disgust. Sellers can benefit from marketing remanufactured consumer products through physical channels (i.e., brick‐and‐mortar, outlet, showroom stores) as opposed to solely through online channels, which is the common practice among many sellers.